Study of lung cancer prevention by Euglena gracilis extracts - Upreti, Deepa (Kansas State University, 2022)
Lung cancer is the leading cause of cancer-related deaths. Because traditional treatment measures are associated with several limitations such as severe side effects and complications, natural products could be explored to develop novel preventative and therapeutic strategies against lung cancer. Euglena gracilis (E. gracilis) is a unicellular micro-alga used as a nutritional and functional dietary supplement because of its several health benefits. E. gracilis has long been known to have medicinal properties for multiple diseases including cancer. However, its anti- tumor properties against lung cancer are unknown. This dissertation examined the effect of water extract of Euglena gracilis (EWE) on the growth of lung cancer and demonstrated the mechanisms of its antitumor properties. In the first part of the dissertation, the antitumor and immunomodulatory effects of partially purified water extract from E. gracilis (EWE) against lung cancer were examined. Oral pretreatment with EWE three weeks before the Lewis lung carcinoma (LLC) cell inoculation significantly attenuated the growth of LLC tumors in immunocompetent syngeneic mouse lungs. EWE administration significantly reduced the granulocyte population in mouse peripheral blood and also directly attenuated granulocytic MDSCs (gMDSCs) in primary cell culture with mouse bone marrow cells, which was attributed to the gMDSC-specific apoptosis. These findings indicate that partially purified water extract from E. gracilis contains significant bioactive materials that, when consumed, attenuate the lung tumor growth by stimulating host antitumor immunity. Further, we prepared other fractions by boiling the EWE (bEWE) and then, evaluated the antitumor effects of both EWE and bEWE using orthotopic lung cancer syngeneic mouse models with LLC cells. The treatment with bEWE further attenuated the growth of LLC tumors in the lungs. Since Euglena water extracts were administrated daily via drinking water, there is a likelihood of alteration of intestinal microbiota and/or their metabolites. Therefore, we explored the fecal microbial communities from the mice treated with EWE, bEWE, and PBS using 16S rRNA gene sequencing. A more diverse intestinal microbiota composition in both extract-treated groups than that in the PBS group was observed. Particularly, a decrease in the ratio of Firmicutes to Bacteroidetes and significant increases in Akkermansia and Muribaculum were observed in both EWE- and bEWE-treated groups. The fecal microbiota transplantation (FMT) studies established that the attenuation of lung carcinoma growth in mice by Euglena water extracts is associated with the alteration of the gut microbiota. We also showed the attenuation of lung carcinoma growth using chemical-carcinogen- induced lung tumorigenesis in mice that closely mimics human lung cancer development. The fecal metabolites between the PBS and bEWE treated mice were different. The metabolites such as succinate, malate, triethanolamine, acetylserine, aspartate, glutamate, and threonine that can be metabolized to short-chain fatty acids (SCFAs) were increased with bEWE treatment. More importantly, the levels of fecal SCFAs such as acetate, butyrate, and propionate were increased upon Euglena water extract treatment. Further, an in vitro study showed inhibition of lung cancer growth with SCFAs treatment via apoptosis. Together, these studies elucidate the understanding of the anti-tumor efficacy of the water extracts from E. gracilis on the prevention and treatment of lung carcinoma growth. Further, these studies highlight the role of gut microbiota and its metabolites with the oral administration of E. gracilis water extracts in the attenuation of lung carcinoma growth using different lung carcinoma model. These findings may facilitate the usage of water extracts from E. gracilis for the development of novel prevention and therapeutic strategies against cancers.
Keywords: Water extract from Euglena gracilis; Lung cancer prevention and therapy; Gut microbiota and metabolites alteration; Short-chain fatty acids; Cancer cell apoptosis